Apakah Pemberdayaan Perempuan dalam Ekonomi dan Politik Telah Meningkatkan IPM Perempuan Indonesia? - Abdurrahman, Abdurrahman; Tusianti, Ema (UI Scholars Hub, 2021)
Gender Development Index (GDI) shows that gender development inequality in Indonesia is still high because of lower female Human Development Index (HDI) than that of male. This research is pointed to analyse the impact of women empowerment on economy and politics to female HDI. By using multiple linear regression model and harnessing data of 514 regencies/municipalities, this research reveals that share of women on parliament, women on professional work, and women as entrepreneurs simultaneously affects women HDI in Indonesia.